Vitamin D(3) Supplementation Decreases a Unique Circulating Monocyte Cholesterol Pool in Patients with Type 2 Diabetes - Riek, Amy E. (J Steroid Biochem Mol Biol, 2017)
Cross-sectional studies indicate consistent associations between low 25(OH)D concentration and increased risk of cardiovascular disease (CVD), but results of randomized control trials (RCTs) are mixed. However, the majority of the RCTs do not focus on type 2 diabetics, potentially obscuring the effects of vitamin D in this population. In vitro 1,25(OH)(2)D(3) downregulates macrophage cholesterol deposition, but the in vivo effects are unknown. To explore potential mechanisms of the effects of vitamin D on CVD risk in patients with type 2 diabetes, we isolated monocytes in a subset of 26 patients from our RCT of diabetics with baseline serum 25(OH)D <25 ng/mL randomized to vitamin D(3) 4000 IU/day or placebo for 4 months. Upon enrollment, the mean 25(OH)D level was 17 ng/mL, which increased to 36 ng/mL after vitamin D and remained unchanged in the placebo group. Before randomization, groups demonstrated similar mean hemoglobin A1c and plasma lipids levels, none of which was significantly altered by vitamin D supplementation. Moreover, assessment of oxidized LDL uptake in monocytes cultured in the patient’s own serum before vs. after treatment resulted in >50% reduction in the vitamin D group with no change in the placebo group. This was mediated through suppression of endoplasmic reticulum stress and scavenger receptor CD36 protein expression. The reduction in monocyte cholesterol uptake was reflected in a 19% decrease in total monocyte cholesterol content. Interestingly, cross-sectional analysis of circulating monocytes from vitamin D-deficient vs. sufficient diabetic patients revealed 8-fold higher cholesteryl ester content, confirming the capacity of these monocytes to uptake and carry cholesterol in the circulation. This study identifies a unique circulating cholesterol pool within monocytes that is modulated by vitamin D and has the potential to contribute to CVD in type 2 diabetes.